Degradation of diclofenac by Fe(II)-activated peracetic acid. Issue 27 (6th December 2021) - Wang, Zhenran; Shi, Hongle; Wang, Shixiang; Liu, Yiqing; Fu, Yongsheng
ABSTRACT: In this study, peracetic acid (PAA) activated by Fe(II) was proposed to remove diclofenac (DCF) in polluted water. It was found that Fe(II)/PAA system could effectively remove DCF at neutral condition, which has a significant advantage over classical Fenton process. According to the result of scavenging experiment, both hydroxyl radical and peroxy radical were considered to be responsible for the degradation of DCF. The influence of several operational parameters including initial pH, Fe(II) dosage, PAA concentration and common water matrix on DCF removal were investigated. 80% DCF was removed at mild condition (pH 6–7) within 60 s, and its removal rate could be enhanced with the increase in Fe(II) dosage and PAA concentration. Presence of H C O 3 − and natural organic matter (NOM) was proved to have a significantly negative impact on DCF degradation. Four probable degradation pathways of DCF were proposed based on the detected reaction products, including hydroxylation, C–N bond cleavage, decarboxylation and dehydrogenation. GRAPHICAL ABSTRACT: UF0001